(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Valve replacement is a surgical procedure. By this procedure, the dying risks are significantly less (1-3%). If the person continues with the problem, it may lead to death. Depending on the patient, either a biological or mechanical valve can be changed. After replacement, the patient must take an Acitrome tablet. Acitrome is a blood-thinning medication till the patient uses an Acitrome tablet. For the rest of his or her life, he or she must eat only one green leafy vegetable per week.